Modernization of ships for launching ultra-precision weapons in the conditions of modern warfare - Argunov, Sergey A. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The most modern shipbuilding issues concerning stealth technology in navy ships are focused on wake and acoustic signature reduction, reduction of visibility of ships and submarines as well as of their displacement. Special materials and alloys are used in shipbuilding for such purposes. In solving a wide range of such issues, a special emphasis has been placed on equipping vessels with up-to-date missile and artillery systems, antiaircraft defence systems and electronic warfare and radar systems. The multifunctionality of Navy vessels becomes the main criterion for their combat deployment.